Accuracy of postmortem radiography of excised air-inflated human lungs in assessment of pulmonary emphysema. Issue 12 (December 1982) - Sutinen, S; Lohela, P; Pääkkö, P; Lahti, R
Abstract : The accuracy of radiography of excised air-inflated lungs in assessing pulmonary emphysema at necropsy was evaluated in a series of 107 adults who had died in hospital by reading the radiographs and examining the pathological specimens independently. The radiographic and pathological assessments of the severity of emphysema correlated significantly (r = 0.87, p less than 0.0001). Mild emphysema was recognised radiographically in 88.7% and moderate in 94.9% of the lungs. One of 16 normal lungs (6.3%) was radiographically diagnosed as showing mild emphysema. Six out of 53 lungs (11.3%) with mild emphysema were radiographically assessed as normal. The correct radiographic recognition of the type of emphysema was possible in 86% of lungs with mild and 97.4% with moderate centrilobular emphysema and in 81.8% and 87.5% respectively of the lungs with mild and moderate paracicatricial emphysema, but in only 25.0% and 28.6% of the lungs with mild and moderate panlobular emphysema. Radiographical diagnosis of centrilobular and paracicatricial emphysema was verified pathologically in all lungs showing mild emphysema, but that of panlobular emphysema in only 66.7%. Radiography of excised air-inflated lungs is a rapid, convenient, and reliable method of recognising and assessing the severity of appreciable degrees of centrilobular and paracicatricial emphysema, but less reliable in recognising panlobular emphysema. After the procedure the specimen remains available for almost any other technique.